Expression and potential role of CXCL5 in the pathogenesis of intrauterine adhesions - Zi-Ang Fang; Yu He; Chao Sun; Lei Zhan; Guiju Zhou; Bing Wei; Shiying Sun (Journal of International Medical Research, 2021)
Objective C-X-C motif chemokine ligand 5 (CXCL5), a member of the chemokine family, is associated with remodeling of connective tissues. However, its role in formation of intrauterine adhesions (IUA) remains unclear. We aimed to investigate the expression and mechanism underlying the role of CXCL5 in IUA. Methods Expression of CXCL5 in IUA was detected by immunohistochemistry in a rat model of IUA and by real-time PCR and western blotting in patients with IUA. The protein levels of matrix metalloproteinase 9 (MMP9) and transcription factor p65 in human endometrial cells were assessed by western blotting after CXCL5 overexpression. Results Protein expression of CXCL5 was significantly decreased in the endometria of IUA rats compared with that of control and sham-operated rats. Real-time PCR and western blotting in patients with IUA showed similar results to those from the rat model. After overexpression, CXCL5 significantly upregulated expression of MMP9 and slightly upregulated expression of p65 in human endometrial cells. Conclusions CXCL5 plays an important role in IUA formation after endometrial injury. We propose a molecular mechanism to explain formation of IUA, including downregulation of MMP9 by low CXCL5 expression. These findings provide valuable information for the prevention and targeted therapy of IUA.